Florence Hamilton collection relating to Edwin Markham - Hamilton, Florence; Markham, Edwin, 1852-1940.
Correspondence, Markham's poetry, articles and speeches, biographical materials, scrapbooks, printed matter, photographs, memorabilia, and other papers pertaining chiefly to the poet Edwin Markham (1852-1940), collected by Florence Hamilton. Includes Hamilton's correspondence with Markham, correspondence of Markham's wife, Anna Catherine Markham, Hamilton's unpublished biography of him, and notes and writings on Markham by others. Subjects include Markham's lecture tours, stays with Charles R. Walgreen and Myrtle R. Norton Walgreen, poetry of others, social and religious issues, William Dean Howells, Hamilton's life as a poet in New York, the relationship between Markham and Hamilton, and their personal affairs.
Library of Congress Prints and Photographs Division.
Poet and lecturer. Born 1873; died 1968.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Howells, William Dean, -- 1837-1920.; Markham, Anna Catherine, -- 1859-1938 -- Correspondence; Markham, Edwin, -- 1852-1940.; Markham, Edwin, -- 1852-1940 -- Correspondence; Walgreen, Charles R. -- 1873-1939.; Walgreen, Myrtle R. Norton, -- 1879-; Literature; Poetry; New York (State) -- Social life and customs; United States -- Religion; United States -- Social conditions; Lecturers; Poets